2016
DOI: 10.1038/srep38180
|View full text |Cite
|
Sign up to set email alerts
|

Increased hepatocellular carcinoma risk in chronic hepatitis B patients with persistently elevated serum total bile acid: a retrospective cohort study

Abstract: To investigate the association between long-term changes of serum total bile acid and hepatocellular carcinoma in chronic hepatitis B patients, we did a retrospective cohort study of 2262 chronic hepatitis B patients with regular antiviral treatment using data from the Hepatitis Biobank at Southwest Hospital Program from 2004 to 2014. Patients in the study were classified into 3 groups according to persistence of elevated serum total bile acid during follow-up: none-low, medium, and high persistence of elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…After adjustment, TBA and PIVKA-II were two variables that significantly influence the incidence of HCC for the most at-risk population and the hazard ratios were 1.918 (95% CI: 1.111–3.310, P = 0.019) and 0.433(95% CI: 0.277–0.678, P < 0.001). This was consistent with our previous study that constant high level of TBA increased the risk of HCC [ 25 ].…”
Section: Resultssupporting
confidence: 94%
“…After adjustment, TBA and PIVKA-II were two variables that significantly influence the incidence of HCC for the most at-risk population and the hazard ratios were 1.918 (95% CI: 1.111–3.310, P = 0.019) and 0.433(95% CI: 0.277–0.678, P < 0.001). This was consistent with our previous study that constant high level of TBA increased the risk of HCC [ 25 ].…”
Section: Resultssupporting
confidence: 94%
“…2b 27 p : vaccination protection rate per year;0.85 (0.75−0.95) 20, 21, 27, 40 ε : perinatal infection rate per year;0.06 (0.03−0.09) 34–37 w : proportion of HBsAg positive mothers in the total prevalence of HBsAg aged 15–49 years;0.8491 (Calculated according to survey data in 1992) 15 q p :proportion of acute HBV infections that became chronic during delivery period;0.90 1, 34, 36 m a : age-specific mortality rate of HBV-related diseases per year;See Fig. 2c 21, 2933 d a ( t ): age-specific total death rate in year t ;See Fig. 2d 22–26 1990 ≤  t  ≤ 1995 d a ( t ) =  d a (1990),1996 ≤  t  ≤ 2002 d a ( t ) =  d a (2000),2003 ≤  t  ≤ 2007 d a ( t ) =  d a (2005),2008 ≤  t  ≤ 2014 d a ( t ) =  d a (2010). μ a ( t ): age-specific death rate of non-HBV related diseases in year t ; μ a ( t ) = ( d a ( t ) N a ( t ) −  m a C a ( t ))/ N a ( t ) 21–26, 2933 θ a ( t ): catch-up vaccination coverage rate for adolescents in year t ;0.95 (For population aged 8–15 years in 2009–2011). 28 q a : age-specific proportion of acute HBV infections that became chronic per year; 1, 34, 36 0 ≤  a  < 1 year0.301 ≤  a  ≤ 4 years0.255 ≤  a  ≤ 15 years0.0616 ≤  a  ≤ 100 years0.03 β a (1992): age-specific transmission rate of HBV in 1992.See Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2c 21, 2933 d a ( t ): age-specific total death rate in year t ;See Fig. 2d 22–26 1990 ≤  t  ≤ 1995 d a ( t ) =  d a (1990),1996 ≤  t  ≤ 2002 d a ( t ) =  d a (2000),2003 ≤  t  ≤ 2007 d a ( t ) =  d a (2005),2008 ≤  t  ≤ 2014 d a ( t ) =  d a (2010). μ a ( t ): age-specific death rate of non-HBV related diseases in year t ; μ a ( t ) = ( d a ( t ) N a ( t ) −  m a C a ( t ))/ N a ( t ) 21–26, 2933 θ a ( t ): catch-up vaccination coverage rate for adolescents in year t ;0.95 (For population aged 8–15 years in 2009–2011). 28 q a : age-specific proportion of acute HBV infections that became chronic per year; 1, 34, 36 0 ≤  a  < 1 year0.301 ≤  a  ≤ 4 years0.255 ≤  a  ≤ 15 years0.0616 ≤  a  ≤ 100 years0.03 β a (1992): age-specific transmission rate of HBV in 1992.See Fig. 2e 15, 40

Note.

…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors including the gut microbiota (5), bile salt transporters (6) and nuclear receptor farnesoid-X-receptor (FXR) (7), participate in the regulation of BA homeostasis. Chronic cholestasis leads to fibrosis, cirrhosis, and eventually liver failure and hepatocellular/cholangiocellular carcinomas (7,8). Recent studies have shown that alterations in BA homeostasis occur in liver diseases.…”
Section: Introductionmentioning
confidence: 99%